O14 Attitudes towards HPV vaccination for boys among sexual health clinicians. (18th May 2015) - Draeger, Eleanor; McSorley, John; Greenhouse, Peter; Clarke, Janette
Abstract : Background: In 2014 the JCVI issued an interim position statement recommending HPV vaccination for MSM under 40 through GUM clinics. BASHH advocates universal HPV vaccination. Aim: We sought sexual health clinicians' opinions on HPV vaccination of males. Methods: Online anonymous survey, circulated via BASHH. Results: 131 responses – 90 (68.7%) female. 95 (75%) doctors; 19 (14%) nurses; 8 (6%) health advisors; 9 (7%) Other. 117/124 (95%) thought there should be universal HPV vaccination. 114/118 (97%) would vaccinate a daughter, 24/27 (88%) of those with an eligible daughter had done so. 107/119 (90%) would vaccinate a son, 10/24 (42%) with a teenage son have done so. 118 (90%) support a catch up programme. 96 (73%) thought this should include all boys up to age 18. 117 (89%) thought that MSM and others should also be vaccinated. 65/120 (54%) of respondents' clinics are offering (40/120) or plan to offer (25/120) HPV vaccine to MSM (Table 1). Discussion: Sexual health clinicians overwhelmingly recommend HPV vaccination of all schoolchildren. They support a targeted HPV vaccination programme in MSM within GUM services but are concerned that this strategy alone is too late and too limited.